PENGEMBANGAN MODUL FLIPBOOK DIGITAL UNTUK MAHASISWA S1 PENDIDIKAN IPA - Rohmatus Syafi'ah; Aldila Wanda Nugraha (Universitas Bhinneka PGRI, 2024)
Development of digital flipbook modules for integrated science learning courses for undergraduate students of science education. Teaching materials for integrated science learning courses in the Bachelor of Science Education Study Program at Bhinneka PGRI University are still limited in the form of powerpoint (PPT). Researchers intend to add references and make it easier for students to access them online by developing digital flipbooks. The digital flipbook is equipped with an active link that is synchronized on the Learning Management System (LMS) of the lecturer. The goal is for students to easily access references without time and space restrictions. The development refers to the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). Data collection uses a questionnaire instrument. The test subjects were 10 students of the science education study program at Bhinneka PGRI University. The results of the validation of the module developed in the dimensions of material content, language, and graphics reached an average coefficient of 0.875 very valid. Responsse to the dimensions of usefulness, attractiveness, ease, understanding, and sentence structure obtained an average percentage of questionnaire results of 87% very good category. The conclusion in this study is that the module in the form of a digital flipbook of Integrated Science Learning courses can be applied in learning activities in universities.